Histomorphometrical Study of Placental from Male and Female Neonates of Diabetic Women - Mahmoud, Estabraq A.; Al-Bakri, Nahla A.; Qasim, Ban J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Objective: To investigate occur the histomatrical alternations in placental terminal villi and their vessels of Iraqi diabetes (gestational diabetes and overt diabetes) and normal pregnancies were born male and female neonates. Methods: The hitometrical study of male and female terminal villi of 68 placentae in maternal diabetes mellitus (34 gestational diabetes, 34 overt diabetes (17 DM type 1 and 17 DM type 2) and 34 normal placentae. These placentae obtained from Department of Obstetrics and Gynaecology in three hospitals in Baghdad city. Results: The study showed that there is a statistically significant with higher diameter in central and peripheral sections of the terminal villi and their vessels in male neonate. Moreover, terminal villous diameter in central and peripheral sections of placentae in both male and female neonates appeared highly significant differences (Pâ‰¤0.001) between DM type 1 and DM type 2, but fetal blood vessels in this terminal villous did not record any significant difference (P>0.05). Conclusions: The current results concluded that increasing in diameters terminal villous and their fetal blood vessels of central and peripheral sections of placentae recorded increasing diameters of GDM peripheral sections of placentae in male neonate in comparison to placental sections of other study groups.